Clinical Features and Diagnostic Strategies for Polycystic Ovary Syndrome (PCOS) in Bahawalpur, Pakistan - Munazzah Marryum; Khawar Ali Shahzad; Muhammad Faizan Munawer; Mavra Saleem; Shabana Ramzan; Muhammad Rashid (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2025)
The aim is to outline the research methodology employed for diagnosing and classifying Polycystic Ovary Syndrome (PCOS) patients while offering guidance on the management and potential cure of PCOS, ultimately facilitating the ability of affected women to conceive. The methodology in this research included multiple steps: firstly, a physical examination based on clinical features; secondly, verification of the disease using biochemical tests and ultrasound. The study included 54 female patients seeking fertility assistance, utilizing physical examination, biochemical tests, and ultrasound to diagnose PCOS. The data were collected at Bahawal Victoria Hospital, Bahawalpur, Pakistan; fifty-four patients were analyzed based on clinical features, biochemical parameters, and ultrasonography. The study revealed strong correlations between PCOS and hirsutism, oligomenorrhea, family PCOS history, and acne. Unmarried women faced a higher PCOS risk. The most common features were oligomenorrhea (90.7%) and hirsutism (83.3%), followed by amenorrhea (57.4%), family history (55.6%), and acne (53.8%). All these factors showed significant associations with PCOS (p < 0.001 for hirsutism, oligomenorrhea, and family history, while p = 0.002 for acne). A positive correlation was found among patients with PCOS who had BMI, hirsutism, a family history, and acne. The research at Bahawal Victoria Hospital, Pakistan, employed diverse diagnostic tools to observe and categorize 54 patients, demonstrating early PCOS diagnosis effectiveness and manageability through medication and lifestyle changes for infertility. This study highlights the importance of integrating clinical, biochemical, and ultrasonographic features for the accurate diagnosis of PCOS. Early diagnosis and targeted management can significantly improve outcomes for affected women.